Psychotherapy in the era of artificial intelligence: Therapist Panoptes - Brailas, Alexios (Homo Virtualis, 2019)
“What will happen when an artificial intelligence entity has access to all the information stored about me online, with the ability to process my information efficiently and flawlessly? Will such an entity not be, in fact, my ideal therapist?” Would there ever come a point at which you would put your trust in an omniscient, apperceptive, and ultra-intelligent robotic therapist? There is a horizon beyond which we can neither see nor even imagine; this is the technological singularity moment for psychotherapy. If human intelligence is capable of creating an artificial intelligence that surpasses its creators, then this intelligence would, in turn, be able to create an even superior next-generation intelligence. An inevitable positive feedback loop would lead to an exponential intelligence growth rate. In the present paper, we introduce the term Therapist Panoptes as a working hypothesis to investigate the implications for psychotherapy of an artificial therapeutic agent: one that is able to access all available data for a potential client and process these with an inconceivably superior intelligence. Although this opens a new perspective on the future of psychotherapy, the sensitive dependence of complex techno-social systems on their initial conditions renders any prediction impossible. Artificial intelligence and humans form a bio-techno-social system, and the evolution of the participating actors in this complex super-organism depends upon their individual action, as well as upon each actor being a coevolving part of a self-organized whole.